Isolasi Senyawa Metabolit Sekunder Fraksi N- Heksana Dari Daun Pegagan (Centellaasiatica L.) Dan Uji Antibakteri Terhadap Mycobacterium tuberculosis - Salmiwanti Salmiwanti; Asriani Ilyas; Asri Saleh (Al-Kimia, 2016)
Centella (Centella asiatica L. Urb) is one of the wild plants which are found in Indonesia and used by the community as a medicine. This study aims to isolate the kind of compound contained in n-hexane fraction centella asiatica leaf and to determine the optimal concentration of bioactive compounds gotu kola leaves in inhibiting the growth of bacteria Mycobacterium tuberculosis. centella asiatica leaf  methanol extract obtained by maceration using methanol, then evaporated with a rotary evaporator. extract is then partitioned with n-hexane. n-hexane fraction obtained is evaporated until thick and then proceed to the stage fractionation, purification and identification with phytochemical test, analysis of UV-VIS spectroscopy and FTIR. isolated compounds were then tested antibacterial bioactivity using MODS. the results showed the compound n-hexane fraction contained in centella asiatica leaves are compound alkaloids. Antibacterial test results bioactive compounds of centella asiatica leaf can inhibit the growth of bacteria Mycobacterium tuberculosis optimally at a concentration of 60%, 80% and 100%, which is characterized by the absence of bacterial growth.